Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors

Calculator Output

Simplifying
(y + 9)(y + -2) = 4y

Reorder the terms:
(9 + y)(y + -2) = 4y

Reorder the terms:
(9 + y)(-2 + y) = 4y

Multiply (9 + y) * (-2 + y)
(9(-2 + y) + y(-2 + y)) = 4y
((-2 * 9 + y * 9) + y(-2 + y)) = 4y
((-18 + 9y) + y(-2 + y)) = 4y
(-18 + 9y + (-2 * y + y * y)) = 4y
(-18 + 9y + (-2y + y2)) = 4y

Combine like terms: 9y + -2y = 7y
(-18 + 7y + y2) = 4y

Solving
-18 + 7y + y2 = 4y

Solving for variable 'y'.

Reorder the terms:
-18 + 7y + -4y + y2 = 4y + -4y

Combine like terms: 7y + -4y = 3y
-18 + 3y + y2 = 4y + -4y

Combine like terms: 4y + -4y = 0
-18 + 3y + y2 = 0

Factor a trinomial.
(-6 + -1y)(3 + -1y) = 0

Subproblem 1

Set the factor '(-6 + -1y)' equal to zero and attempt to solve: Simplifying -6 + -1y = 0 Solving -6 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1y = 0 + 6 -1y = 0 + 6 Combine like terms: 0 + 6 = 6 -1y = 6 Divide each side by '-1'. y = -6 Simplifying y = -6

Subproblem 2

Set the factor '(3 + -1y)' equal to zero and attempt to solve: Simplifying 3 + -1y = 0 Solving 3 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 0 + -3 -1y = 0 + -3 Combine like terms: 0 + -3 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3

Solution

y = {-6, 3}
Processing time: 1 ms. 52786911 equations since February 08, 2004.   Disclaimer

Equation Factoring Calculator

Equation: Variable:
       


Hint: Selecting "AUTO" in the variable box will make the calculator automatically solve for the first variable it sees.

Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors